Reputational Herding in Financial Markets: A Laboratory Experiment. Issue 3 (2nd July 2016) - Roider, Andreas; Voskort, Andrea
ABSTRACT: We study reputational herding in financial markets in a laboratory experiment. In the spirit of Dasgupta and Prat [2008], career concerns are introduced in a sequential asset market where wages for investors are set by subjects in the role of employers. Employers can observe investment behavior, but not investors' ability types. Thereby, reputational incentives may arise endogenously. We find that a sizable fraction of investors follows an established trend even in a setting where there are no reputational incentives. In a setting where there are reputational concerns, they do not seem to create substantial herd behavior.